Building a web-based learning (E-Learning) for suburban primary school teachers in Muara Bangkahulu District, Bengkulu City - Boko Susilo Sukendro Mandoyo; Rusdi Efendi; Syafdi Maizora (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
Web-based learning media (e-learning) is a very urgent aids to be provided by the educators in the era of information and communication technology. The main problem in suburban elementary school teacher sub district of Muara Bangkahulu Bengkulu city is the inability of the teachers in using the Internet facilities to be empowered as a learning tool. Therefore, the need to do the training to teachers integrated and comprehensively in the using of the Internet as a learning medium. IbM is partnering with the activities of the working group (“Pokja”) under the basic principal office of the National Education Bengkulu city. There were 41 participants from 8 Elementary School teachers are invited to participate in the creation of e -learning training. In the implementation of the activities there are 23 teacher participants. The training material consists of the introduction of Ms. Word-Ms. Power Point, Internet, blog and manufacture of web-based learning using the Internet service on www.wordpress.com site . The primary outcome of the training is teaching media in each blog site under the site www.wordpress.com. The result is 18 teachers to upload teaching materials in each of his web blog. The results of the monitor until the beginning of November 2013 there were 16 teachers who actively manage his web blog as a medium of learning.